2022
DOI: 10.1002/14651858.cd001245.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Antifibrinolytic therapy for aneurysmal subarachnoid haemorrhage

Abstract: BackgroundRebleeding is an important cause of death and disability in people with aneurysmal subarachnoid haemorrhage. Rebleeding is probably related to the dissolution of the blood clot at the site of the aneurysm rupture by natural fibrinolytic activity. This review is an update of previously published Cochrane Reviews. ObjectivesTo assess the effects of antifibrinolytic treatment in people with aneurysmal subarachnoid haemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…40 Beside the above-mentioned clinical settings characterized by acute hemorrhage, a recent Cochrane systematic review has assessed the effects of antifibrinolytic treatment in patients with hemorrhages due to subarachnoid aneurysms (11 RCTs included involving 2,717 participants). 41 Although antifibrinolytic drugs reduced the risk of rebleeding (RR: 0.65; 95% CI: 0.47–0.91), no significant effect was observed on mortality. Accordingly, the authors concluded that the routine use of antifibrinolytic drugs in the treatment of aneurysmal subarachnoid hemorrhage is not supported by current evidence.…”
Section: Txa In Acute Hemorrhagementioning
confidence: 97%
“…40 Beside the above-mentioned clinical settings characterized by acute hemorrhage, a recent Cochrane systematic review has assessed the effects of antifibrinolytic treatment in patients with hemorrhages due to subarachnoid aneurysms (11 RCTs included involving 2,717 participants). 41 Although antifibrinolytic drugs reduced the risk of rebleeding (RR: 0.65; 95% CI: 0.47–0.91), no significant effect was observed on mortality. Accordingly, the authors concluded that the routine use of antifibrinolytic drugs in the treatment of aneurysmal subarachnoid hemorrhage is not supported by current evidence.…”
Section: Txa In Acute Hemorrhagementioning
confidence: 97%
“…We recommend a target of ≥10 g/dL in the acute phase of IAR. Tranexamic acid. While tranexamic acid reduces rebleeding in patients with SAH, it does not improve overall outcomes 31 . It cannot be recommended for IAR based on currently available evidence. Inspired oxygen fraction (FiO 2 ).…”
Section: Anesthesia Management During Iarmentioning
confidence: 97%
“…While tranexamic acid reduces rebleeding in patients with SAH, it does not improve overall outcomes. 31 It cannot be recommended for IAR based on currently available evidence. • Inspired oxygen fraction (FiO 2 ).…”
Section: Anesthesia Management During Iarmentioning
confidence: 99%
“…The ULtra-early TRranexamic Acid after Subarachnoid Hemorrhage (ULTRA) trial provided convincing evidence that even very early and very short lasting antifibrinolytic therapy does not eliminate the risk of early rebleeding and does not improve functional outcome in patients with aSAH. An updated Cochrane review on this subject concluded that the current evidence does not support the routine use of antifibrinolytic drugs in patients with aSAH [ 22 ]. The recent Neurocritical Care Society guideline also recommends against the administration of antifibrinolytic therapy to prevent rebleeding of ruptured aneurysms in patients with aSAH [ 23 ].…”
Section: Introductionmentioning
confidence: 99%